2019
DOI: 10.1111/scd.12399
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic pain associated with an odontogenic infection: An unusual Lemierre's syndrome

Abstract: Lemierre's syndrome is characterized by thrombophlebitis in the internal jugular vein after an infection in the area of the head or neck, mostly in the form of pharyngitis and/or tonsillitis. It may also result from less common conditions, such as odontogenic infections, but this condition has not often been reported in the dental literature. The syndrome's main etiological agent is Fusobacterium necrophorum, and it most commonly occurs in young adults. This study reports the clinical case of a 34‐year‐old fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It is a complication that can rarely be seen with the progression of complications such as sepsis and septic embolization of the lung secondary to anaerobic infection in the head and neck area, but its clinical course is fatal. 77 , 78 …”
Section: Clinical and Research Consequences: Complications Associated...mentioning
confidence: 99%
See 3 more Smart Citations
“…It is a complication that can rarely be seen with the progression of complications such as sepsis and septic embolization of the lung secondary to anaerobic infection in the head and neck area, but its clinical course is fatal. 77 , 78 …”
Section: Clinical and Research Consequences: Complications Associated...mentioning
confidence: 99%
“… 82 This syndrome is known to be more common in young adults; it is seen at lower rates, especially with the widespread use of antibiotics to treat streptococcal pharyngitis. 78 …”
Section: Clinical and Research Consequences: Complications Associated...mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review found that 73% had experienced signs or symptoms of a recent acute oropharyngeal infection, though other sites of infection including the ear, lower respiratory tract, and neck were also reported [ 9 ]. Other primary infections such as cellulitis [ 33 ], perianal abscess [ 34 ], and pericoronitis have also been previously reported within the literature [ 35 ].…”
Section: Reviewmentioning
confidence: 99%